Integrative Analysis of Methylation and Gene Expression in Lung Adenocarcinoma and Squamous Cell Lung Carcinoma - Zhang, Hao; Jin, Zhou; Cheng, Ling; Zhang, Bin (Frontiers in Bioengineering and Biotechnology, 2020)
Lung cancer is a highly prevalent type of cancer with poor 5-year survival rate of about 4-17%. 80% lung cancer belongs to non-small-cell lung cancer (NSCLC). For a long time, the treatment of NSCLC is mostly guided by tumor stage, and there is no significant difference between the therapy strategy of lung adenocarcinoma (LUAD) and squamous cell lung carcinoma (SCLC), the two major subtypes of NSCLC. In recent years, important molecular differences between LUAD and SCLC are increasingly identified, indicating that targeted therapy will be more and more histologically specific in the future. To investigate the LUAD and SCLC difference on multi-omics scale, we analyzed the methylation and gene expression data together. With Boruta method to remove irrelevant features and MCFS (Monte Carlo Feature Selection) method to identify the significantly important features, we identified 113 key methylation features and 23 key gene expression features. HNF1B and TP63 were found to be dysfunctional on both methylation and gene expression levels. The experimentally determined interaction network suggested that TP63 may play an important role in connecting methylation genes and expression genes. Many of the discovered signature genes have been supported by literatures. Our results may provide directions of precision diagnose and therapy of LUAD and SCLC.